Managing Value Added Tax Issues in Indonesian Business Entities post-IFRS 15 Adoption - Saptono, Prianto Budi; Khozen, Ismail (UI Scholars Hub, 2022)
This study analyzes challenges related to value-added tax (VAT) transactions in Indonesia following the convergence of International Financial Reporting Standards 15 (IFRS 15) into Statements of Financial Accounting Standards 72 (SFAS or